SULAIMAN AL-QANUNI: SULTAN TERBESAR KERAJAAN TURKI USMANI - Dwi Ratnasari (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2013)
Sultan Sulaiman I is the greatest Muslim statesman of his time. The title "Al- Qanuni" was awarded for his services in establishing the laws of the Islamic Ottoman Empire. His reign was the longest compared to those of other Sultans, namely forty-four years. During his reign, the Ottoman Empire reached its peak of development. Sulaiman managed to conduct a military expedition to Europe, seized Vienna, Hungary, Persia, and all along the Arabic coastal areas as well as re-seized Hijaz region. Sulaiman was also an artist, more particularly a literary man. His works, among others, were some ghazal and diwan (collections of poems). He also wrote a copy of the Quran using his own handwriting, which is now stored properly in the Great Mosque of Sulaiman. He was an intelligent, fair, noble sultan and did a lot of important policies such as settingOttoman iqtha, preparing the legislation, doing reconciliation, setting the police, and establishing madrassa, schools colleges, and many magnificent buildings, including the Mosque of Sulaimaniyah. The reign of Sulaiman al-Qanuni is the golden era of the Ottoman Empire.Keywords: Sultan Solomon, Ottoman Empire, expansion, civilization progressive